Giving and Responding to Feedback: Guidelines for Authors and Reviewers - Lim, Weng Marc *; Bowman, Carmen (Taylor and Francis Group, 2024)
This article offers guidelines for enhancing scholarly discourse in academic publishing, focusing on effective feedback mechanisms. We present two structured frameworks: REVIEW for reviewers and REACT for authors. The REVIEW framework guides reviewers in providing constructive and insightful feedback, emphasizing thorough reading, theoretical and methodological evaluation, verification of claims and sources, identification of strengths and shortcomings, critical engagement, and clear, constructive writing. The REACT framework assists authors in systematically responding to feedback, covering review, evaluation, addressing feedback, clear communication of revisions, and thanking reviewers. These frameworks aim to improve the quality and impact of scholarly work by fostering productive interactions between authors and reviewers. This latest issue of Activities, Adaptation, and Aging also features eight studies that exemplify the successful application of these guidelines, highlighting their importance in advancing dignified and purposeful living for older adults. The frameworks and accompanying studies demonstrate the journal’s commitment to promoting rigorous peer review and responsive manuscript development in academic publishing.